Health Diagnosis and Safety Precaution of Water Conservancy Facilities Based on PHM. Issue 3 (February 2019) - Shi, Yanwen; Du, Weijia; Xu, Jie; Wang, Xi
Abstract: Safe operation of water conservancy facilities is the important condition to safeguard safe operation of hydraulic engineering, thus health management of water conservancy facilities can be ignored. In this thesis, the author applies PHM to health management of water conservancy facilities, constructs health diagnosis and safety precaution system of water conservancy facilities based on PHM, analyzes the system framework and functions, and provides reference for safe operation of hydraulic engineering in China.